6-4x=5x-12

Simple and best practice solution for 6-4x=5x-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-4x=5x-12 equation:


Simplifying
6 + -4x = 5x + -12

Reorder the terms:
6 + -4x = -12 + 5x

Solving
6 + -4x = -12 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
6 + -4x + -5x = -12 + 5x + -5x

Combine like terms: -4x + -5x = -9x
6 + -9x = -12 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 + -9x = -12 + 0
6 + -9x = -12

Add '-6' to each side of the equation.
6 + -6 + -9x = -12 + -6

Combine like terms: 6 + -6 = 0
0 + -9x = -12 + -6
-9x = -12 + -6

Combine like terms: -12 + -6 = -18
-9x = -18

Divide each side by '-9'.
x = 2

Simplifying
x = 2

See similar equations:

| 2(c+3)=-9 | | 4r^3+11r^2-3r=0 | | 2(m-7)=4 | | -47-11x=-3x+73 | | 8x+3+2x+17=180 | | 14x-32=24 | | 5-.666x=1 | | 0.2x+0.3=-0.5 | | -6-20=2n+4(1-3n) | | y=7.50x+25 | | 6-.25x=9 | | 2x^2+4x^3+x^4=0 | | -47-11x=-33x+73 | | 3-2*(x+2)=3 | | 19x+10=87 | | 4a-2=26 | | x-76=-4x+64 | | 32=y*(y+4) | | 2x-14x=3 | | 2x+15=115 | | 4m-13=19 | | 7-.33x=9 | | 5(3x+2)-4=87 | | 4(3x+4)3=6 | | 7-0.75x=9 | | 5(3x+2)-4=47 | | x^2-5x=3(x-5) | | lnx^3-5lnx=1 | | 8-19x=350 | | 7-.75x=9 | | 8x+7y=3.37 | | 2x-3.2x=16 |

Equations solver categories